(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Sustainable Development Goal-11 envisions making cities and human settlements inclusive, safe, resilient and sustainable. This includes sustainable transport in the context of infrastructure, public transport systems, good delivery networks, affordability, efficiency and convenience of transportation, improving urban air quality and health and reducing greenhouse gas emissions. Warm mix asphalt (WMA) and reclaimed asphalt pavement (RAP) are the most leading sustainable materials in asphalt concrete pavements. WMA has been in use for quite some time; however, innovations and increased usage have been stimulated by the greater emphasis on sustainable infrastructure systems. WMA enables decreased production temperatures with the help of wax, water, or other chemicals. The effects of decreased production temperatures include lowered fuel use and emissions, improved compaction, and possible RAP concentration rises. RAP is the recycled product of the old asphalt concrete pavements, and its use leads to trimming in new aggregate and asphalt requirements. However, substantial performance issues can rise from the incorporation of WMA or RAP materials in asphalt concrete. This study assesses the prospects of WMA technologies and their integration with RAP. Initially, a detailed literature review was done to understand the advantages, disadvantages, and past field and lab performance of WMA and RAP mixtures. Marshall Tests, Indirect tensile strength test, aggregate coating and skid resistance tests were conducted on virgin, and varied RAP proportioned mixtures to examine the effects of RAP percentage on Optimum bitumen content, Marshall stability and flow values, aggregate coating and skid resistance. The results of this experiment provided several crucial observations. First, the OBC decreased with an increase in RAP percentage. Secondly, moisture susceptibility, as well as aggregate coating, decreases with the increase in RAP dosage. Furthermore, the inclusion of RAP to WMA mixtures decreased the skid resistance of asphalt concrete as determined by a portable skid resistance tester.